2013
DOI: 10.1021/mp300641h
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl Methylcellulose Mediated Precipitation Inhibition of Sirolimus: From a Screening Campaign to a Proof-of-Concept Human Study

Abstract: The aim of this study was to develop a sirolimus (BCS class II drug substance) solid oral dosage form containing a precipitation inhibitor, which would result in an improved sirolimus absorption in humans compared to the formulation containing nanosized sirolimus without a precipitation inhibitor, i.e., Rapamune. The selection of the precipitation inhibitor was based on the results of a screening campaign that identified two "hit" excipients: HPMC 603 (i.e., Pharmacoat 603) and Poloxamer 407. However, in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Solid dispersions of HPMC and sirolimus demonstrated significant variation from the neat samples as well as a physical blend. Specifically, the sirolimus peaks at 1680–1640 cm −1 (C=C) and 1760–1670 cm −1 (C=O) in the solid dispersion were far broader than those from the pure drug, which the authors concluded was a result of interaction between the two species . This interaction was suggested to be partly responsible for the two‐fold increase in supersaturation and dissolution in the sirolimus‐HPMC solid dispersion vs the commercially available Rapamune ® nanoparticles.…”
Section: Approaches For Precipitation Inhibitor Selection and Increasmentioning
confidence: 96%
See 2 more Smart Citations
“…Solid dispersions of HPMC and sirolimus demonstrated significant variation from the neat samples as well as a physical blend. Specifically, the sirolimus peaks at 1680–1640 cm −1 (C=C) and 1760–1670 cm −1 (C=O) in the solid dispersion were far broader than those from the pure drug, which the authors concluded was a result of interaction between the two species . This interaction was suggested to be partly responsible for the two‐fold increase in supersaturation and dissolution in the sirolimus‐HPMC solid dispersion vs the commercially available Rapamune ® nanoparticles.…”
Section: Approaches For Precipitation Inhibitor Selection and Increasmentioning
confidence: 96%
“…Petrusevska and colleagues also employed FTIR spectroscopy to investigate the mechanism of interactions between a successful API‐PI formulation: sirolimus and HPMC . Solid dispersions of HPMC and sirolimus demonstrated significant variation from the neat samples as well as a physical blend.…”
Section: Approaches For Precipitation Inhibitor Selection and Increasmentioning
confidence: 99%
See 1 more Smart Citation
“… Abbreviations: n.c.: Non classified; n.a. : Non applicable; MCC: Microcrystalline Celullose; CSD: Colloidal Silicon Dioxide; HPMC: Hydroxypropyl-methylcellulose; PVP: Polivinylpyrrolidone; BCS classification was taken from literature as follows: Progesterone, Tuleu et al 2004 [ 3 ]; Gentamicin, Ito et al 2005 [ 12 ]; Nimesulide, Mudie et al 2012 [ 73 ]; Diazepam, Wu and Bennet 2005 [ 74 ]; Ezetimibe, Taupitz et al 2013 [ 75 ]; Griseofulvin, Lindenberg et al 2010 [ 76 ]; Candesartan Cilexetil, Nekkanti et al 2009 [ 67 ]; Nitrendipine, Takano et al 2006 [ 77 ]; Tetrahydrocurcumin, Wahlang et al 2011 [ 78 ]; Piroxicam, Shohin et al 2014 [ 79 ]; Paliperidone, Pandey et al 2013 [ 80 ]; Sirolimus, Petruševska et al 2013 [ 81 ]; Carbamazepine, Wu and Bennet 2005 [ 74 ]; Puerarin, Li et al 2015 [ 82 ]; Cilostazol, Jinno et al 2006 [ 83 ]; Lercaniditine, Non-classified; Repaglinide, Gao et al 2013 [ 84 ]; Ondansetron, Beg et al 2013 [ 53 ]; Atorvastatin calcium, Wu and Bennet 2005 [ 74 ]; Olmesartan medoxomil, Patel et al 2014 [ 34 ]; Ibuprofen, Cristofoletti and Dressman 2017 [ 85 ]; Furosemide, Vogelpoel et al, 2010 [ 86 ]; Propranolol, Granero et al 2010 [ 87 ]; Oleanolic acid, Tong et al 2011 [ 88 ]; Simvastatin, Jiang et al 2012 [ 60 ]; Glipizide, Zur et al 2015 [ 89 ]; Celecoxib, Yazdanian et al 2005 [ 90 ]; Lercanidipine, Suthar et al 2016 [ 54 ]; LogP values were taken from ref. [ 91 ].…”
Section: Figurementioning
confidence: 99%
“…reported that HPMC effectively created a desired microenviroment that both maintained a supersaturated solution and prevented sirolimus precipitation [10]. In addition, it was observed that in vitro supersaturated dissolution data strongly correlated with in vivo pharmacokinetic parameters [9,10]. In fact, the oral bioavailability of sirolimus can be improved by enhancing in vitro supersaturation via an amorphous solid dispersion.…”
Section: Introductionmentioning
confidence: 99%